KONSEP PENDIDIKAN KELUARGA MENURUT HASAN LANGGULUNG DAN RELEVANSINYA DENGAN PENGEMBANGAN KESEHATAN MENTAL KELUARGA - Harahap, Ahmad Muda (Turast: Jurnal Penelitian dan Pengabdian, 2018)
This article aims to describe and analyze the concept of family education according to Hasan Langgulung and its relevance to the development of family mental health. This study uses a character research method using descriptive qualitative approach. Hasan Lagulung’ concept is as data in this research. The results of the study shows that the six aspects of family education namely physical education and health, intellectual education, emotional education, religious education social education aspects can develop children's potential on cognitive, affective, psychomotor, and spiritual. It is concluded that the development of this potential impacts on family mental health. It implies that if the first aspect does not work well, it impacts on other aspects.